THE ROLE OF GOVERNMENT PROGRAMS IN ELEVATING EAST JAVA MSMES: COMMUNITY PARTICIPATION AND ENTREPRENEURIAL ATTITUDES AS INTERVENING - Sutomo; Setyawati, Amelia; Ibadil Maula, Farij; Wishnu Wardana, Ludi; Binti Mohd Mustamil , Norizah; Sutoyo; Irianto Uripan, Koen (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2024)
Phenomenon/Issue: Following the COVID-19 pandemic, SMEs in East Java have struggled due to limited external support, leading to business declines, increased unemployment, and rising poverty rates. Purpose: This study examines how government and community support affect SME success in East Java, with entrepreneurial attitudes as a moderating factor. Novelty: Applying Social Cognitive Theory, this research uniquely explores how entrepreneurial attitudes amplify the effects of external support on business success, offering fresh insights into the interplay of external and individual influences in driving business performance. Research Methods: This quantitative study analyzes data from SME owners in East Java to assess the roles of government support, community involvement, and entrepreneurial attitudes in achieving business success. Results: Both government and community support have significant, positive impacts on SME success, particularly in areas such as licensing ease and network access. Entrepreneurial attitudes further enhance these effects, fostering adaptability and innovation that strengthen SME competitiveness. Research Contributions: The study underscores the importance of government support, community involvement, and entrepreneurial mindset in bolstering SMEs in East Java, providing key policy recommendations for supporting post-pandemic economic recovery